MANAJEMEN PELAYANAN UMRAH PT. ZAM ZAM UTAMA DALAM MENINGKATKAN KUALITAS WISATA RELIGI (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
The main problem in this study is how the management of PT. Zam Zam Utama's Umrah service improves the quality of religious tourism. In this study there are two formulations of the problem 1) How is the standard of PT. Zam Zam's Umrah service in improving the quality of religious tourism. 2) What are the challenges faced by religious tourism managers in providing services to PT. Zam Zam Utama's Umrah pilgrims? This type of research is descriptive-qualitative with a research approach related to the science of Hajj and Umrah management. The type of data processed is primary data obtained from interviews with six informants: commissioners, secretaries, marketing staff, public relations and documentation, and alumni of PT. Zam-Zam Utama; secondary data analyzed through data collection, data reduction, presentation, and drawing conclusions. The results of this study indicate that the service standards of PT. Zam Zam Utama are four, namely: 1) Manasik services by providing professional and experienced speakers in the field of Umrah so that it is easier for pilgrims to understand during the manasik. 2) Adequate facilities and accommodation, 3) Pilgrim health services; 4) Appointing professional tour guides and tour leaders with professional tour guides and tour leaders will make pilgrims feel satisfied when visiting because the information provided is clear and easy to understand. The challenges faced by religious tourism managers in providing services to Umrah pilgrims are: 1) language differences; 2) completeness of pilgrim files; and 3) delays in pilgrims arriving at the airport. The implications in this study are that PT. Zam Zam Utama is expected to maintain the quality of service standards, especially in determining tour guides and tour leaders, because tour guides and tour leaders can make pilgrims satisfied with the services provided by tour guides and tour leaders.